T209. EFFECTS OF CHRONIC HALOPERIDOL EXPOSURE ON [3H]RO15-4513 AND [3H]FLUMAZENIL GABA-A RECEPTOR BINDING SITES. (18th May 2020) - Peris-Yague, Alba; Kiemes, Amanda; Cash, Diana; Cotel, Marie-Caroline; Singh, Nisha; Vernon, Anthony; Modinos, Gemma
Abstract: Background: Post-mortem studies in schizophrenia (SZ) have reported abnormalities in the GABAergic system, more specifically, on αGABA-A receptors (αGABA-A R) (Benes, Kwok, Vincent, & Todtenkopf, 1998; Beneyto, Abbott, Hashimoto, & Lewis, 2011). Consistently, animal models of SZ have also reported changes in these receptor subtypes (Lodge, Behrens, & Grace, 2009; Richetto, Calabrese, Riva, & Meyer, 2014). Preclinical work in the methylazoxymethanol acetate (MAM) animal model of SZ has shown that administration of an α5GABA-A modulating drug rescues the psychosis-like phenotype (hyperdopaminergia) (Gill, Lodge, Cook, Aras, & Grace, 2011). However, this rescue does not occur if the animals are previously administered the first-generation antipsychotic haloperidol (Gill, Cook, Poe, & Grace, 2014). A recent study in patients with first-episode psychosis found increased baseline GABA levels as measured by magnetic resonance spectroscopy (de la Fuente-Sandoval et al., 2017). After 4 weeks of treatment with the antipsychotic risperidone, these GABA levels normalized in the medial prefrontal cortex and decreased at a trend level in the dorsal caudate (de la Fuente-Sandoval et al., 2017). All in all these studies suggest that antipsychotic medication besides directly regulating the dopaminergic system may also be acting on the GABAergic system, but the underlying mechanisms remain unknown. The aim of our study was thus to investigate, for the first time, the effects of clinically-relevant dosages of haloperidol on α5GABA-A R and benzodiazepine-sensitive α1–3;5GABA-A R in healthy rats. Methods: A total of 36 male Sprague-Dawley rats were treated with vehicle, haloperidol 0.5 mg/kg/day or 2 mg/kg/day with an osmotic minipump for 28 days, representing clinically-relevant dosages of antipsychotic administration (Kapur, Vanderspek, Brownlee, & Nobrega, 2003). Quantitative autoradiography was conducted with [3H]Ro15-4513 and [3H]flumazenil, to assess the effects of haloperidol on α5GABA-A R and overall α1–3;5GABA-A R. Optical density measurements from cortical and subcortical regions were obtained from the autoradiographs using the MCID Software and converted into radioactivity values using a robust linear regression on GraphPad Prism. All data were analyzed using a mixed-effects model ANOVA on the same software and considered significant at p<0.05 with FDR correction for multiple comparisons. Results: Administration of chronic haloperidol showed a dose-specific increase in [3H]Ro15-4513 in the dorsal CA1 area of the hippocampus, showing an increase in binding in the 0.5 mg/kg/day vs. vehicle (p<0.01; q<0.01) and a decrease in the 2 mg/kg/day vs. the 0.5 group (p<0.05; q<0.01). In the nucleus accumbens, there was a significant reduction in [3H]Ro15-4513 binding in the higher-dose group compared to the 0.5 mg/kg/day group (p<0.001; q<0.001). In contrast, haloperidol exposure relayed a general increase in [3H]flumazenil binding across all the regions of interest explored (p<0.05). Discussion: This is the first study to investigate, in healthy rats, the effects of clinically-relevant doses of haloperidol on GABA-A R binding in a receptor-subtype specific manner. Our results show that exposure to haloperidol causes changes in α5GABA-A R predominantly in the dorsal CA1 and the nucleus accumbens. An overall change in benzodiazepine-sensitive α1–3;5GABA-A R is also observed, irrespective of region. These results suggest that exposure to antipsychotic medication impacts the GABAergic system and should be considered when testing new pharmacological strategies in humans that have been exposed to antipsychotic medication.